Enhancing critical care practitioners’ knowledge and adherence to ventilator-associated events bundle: a comprehensive analysis - Alanazi, Samiyah; Alonazi, Wadi B. (Frontiers in Medicine, 2024)
ABSTRACT Objectives: Few surveys have focused on ventilator-associated pneumonia occurring in critically ill patients undergoing intubation and mechanical ventilation. Limited knowledge among healthcare workers may impede compliance with evidence-based guidelines for preventing ventilator-associated pneumonia. We evaluate the knowledge of intensive care professionals related to preventing ventilator-associated pneumonia in the intensive care units. Design: Cross-sectional survey. Setting: Adult critical care departments in four tertiary hospitals in Riyadh in Saudi Arabia. Subjects: Adult intensive care units attending physicians (intensivist, non-intensivist), Nurses, and Respiratory Therapist who works in ICUs. Intervention: None. Measurement and main results: We analyzed 758 questionnaires (100% response rate) from four tertiary hospitals in Riyadh provinces. Nurses constitute the largest group, with most of all professions being Saudi nationals at (343[45.3%]). Physicians are primarily male, accounting for (127[16.8%]), while the Respiratory Therapy field is predominantly female at (91[12%]). Our analysis involved, chi-square test to explore potential variations in knowledge among participants with diverse demographic variables. The finding of this was significant positive correlation between some elements. It provides valuable insights into the intricate associations between demographic characteristics and healthcare practices related to VAP prevention. p < 0.05. Demographic factors significantly influence health practices related to ventilator associated pneumonia bundle prevention. Conclusions: Our research identifies key factors influencing ventilator associated pneumonia prevention in critical care settings and provides actionable recommendations for healthcare institutions to enhance patient safety. While this research has extensively examined physicians, nurses and respiratory therapists, there is a depth of investigations comparing the knowledge and practices of these specialists within tertiary hospitals in Riyadh. Conducting such a study is imperative to address knowledge gaps and promote practices that mitigate the adverse outcomes of ventilator associated pneumonia on healthcare systems. This study underscores the pivotal role of education, professional experience, and demographic factors in shaping medical procedures and practices. Targeted interventions in these areas could potentially enhance adherence to the bundle. The study suggests the importance of targeted education programs, mentorship initiatives, and ongoing research to enhance patient outcomes in critical care settings.